Knowledge of nursing undergraduate students about the use of contact precautions measures - Julielen Salvador dos Santos; Ione Corrêa; Manoel Henrique Salgado (Universidad de Antioquia, 2013)
Objective. To assess knowledge of nursing undergraduate students about the use of contact precautions. Methodology. There were 106 nursing undergraduate students from three universities within the state of Sao Paulo. The data collection was done between April and May 2012. A questionnaire was elaborated with questions assessing knowledge regarding contact precautions. The data were submitted to statistical procedures in the package MINITAB version 16. The knowledge were rated as adequate, partially adequate and inadequate. Results. There was a predominance of females (86%) and age group between 20 and 29 years (70%). Regarding the definition of contact precaution of diseases in which these measures are used, undergraduate's knowledge was partially adequate (92% and 44%, respectively). The knowledge was considered adequate for the preventive measures used during assistance (86%). As difficulties mentioned in the use of these measures were discomfort, lack of material, personnel and time. Conclusion. Although undergraduate students know what measures to be used in contact precaution, they do not have adequate knowledge about which diseases they should use them. The three participating universities should reflect on the quality of training for nursing students regarding biosecurity and contact precautions.